Application of gaming in new media marketing - Mishra, Pratika, 1981-; Dham, Swati Oberoi, 1983- (Business Science Reference, 2019)
"This book captures various aspects of gaming and innovation that is facilitated and can be further improvised by digital innovation. It emphasizes upon areas such as the meaning and relevance of advergaming in marketing, its growth, recent trends, practices, issues and main challenges. It also explores the role of gaming and new media marketing"--